Towards agriculture as career: predicting students' participation in the agricultural sector using an extended model of the theory of planned behavior - Zaremohzzabieh, Zeinab; Krauss, Steven Eric; D’Silva, Jeffrey Lawrence; Tiraieyari, Neda; Ismail, Ismi Arif; Dahalan, Dzuhailmi (Taylor and Francis Group, 2021)
Purpose: The aim of the study was to identify factors associated with tertiary students’ intention to pursue agriculture-related careers. The moderating effect of gender and geographic location on the predictive relationships was also examined. Design/methodology/approach: Quantitative data were collected from 488 students studying in five agricultural-based institutions of higher learning in Malaysia. Structural equation modeling (SEM) was used to analyze the data. Findings: Attitudes towards agriculture, perceived behavioral control, agricultural knowledge, and perception of sustainable agriculture methods predicted students’ intention to join agricultural-related occupations. The results differed according to gender and place of residence for all predictors except conditions of resource facilitation. Practical implications: The findings offer insight into the factors agricultural students consider when deciding whether to pursue careers in agriculture. This can help educational decision-makers respond to the motivational needs of students in recruiting and retention. Theoretical implications: By introducing three new constructs, the study extends application of the theory of planned behavior for predicting intention and behavior in the field of agriculture. Originality/value: The study addresses an important gap on key factors predicting tertiary students’ pursuit of careers in agriculture. A better understanding of factors that shape students’ decision-making about future careers in agriculture can raise critical awareness of where programing efforts are likely to be effective.